Site-Specificity, Pervasive Computing, and the Reading Interface - Farman, Jason (AoIR Selected Papers of Internet Research, 2013)
Through a media archaeology approach, this paper offers a historical grounding for emerging mobile media storytelling projects. By linking these locative media projects to the larger history of attaching narratives to specific places, these projects build on practices that have been done for millennia. From stone inscriptions to the stories that accompany religious pilgrimages, from graffiti in early Rome to historic walking tours of cities, the practice of sited narratives has many precedents. The desire to attach story to space (and to do so through pervasive and mobile computing) is found in the connection between the historical context of a community and the need to determine the character of that space. Around these two points arises a contention over who is actually allowed to tell the story of a location. A site’s dominant narrative is often told through durable while the narratives on the margins are relegated to ephemeral media.